Seeking Solidarity between Protestant and Catholic Churches for Social Justice in Korea: The Case of the Korea Christian Action Organization for Urban Industrial Mission (Saseon) (1976–1989) - Kim, Minah (Religions, 2020)
The Korea Christian Action Organization for Urban Industrial Mission (Hanguk-gyohoe-sahoeseongyo-hyeubuihoe (Saseon)) was an organization which devoted itself not only to the Korean democratization movement against the military dictatorship, but also to the movement for the improvement of the quality of life of laborers, farmers, and the urban poor from 1976 to 1989. Saseon, a joint organization of Protestants and Catholics, trained activists dedicated to democratization and the people’s right to life movements. The Protestants and Catholics of Saseon believed that participation in social movements was missionary work building the Kingdom of God on Earth, and that they could set a good example of solidarity with a common goal of social justice and a mission for the poor which transcended their theological differences. This paper will illuminate the cooperation between Korean Protestant and Catholic churches toward the common goal of social justice, focusing on the case of Saseon.